2000
DOI: 10.2307/524982
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the Gospel of Domesticity: Luhya Girls and the Friends Africa Mission, 1917-1926

Abstract: : Efforts to transform the lives of colonized women and girls were integral to Christian missionary efforts throughout the world. This study of the attempts by a Quaker mission, in what is now Western Province, Kenya, to remake African womanhood indicates the limited success missionaries had in this effort. As with most evangelical missions, “women's work for women” involved domesticating African women and girls. According to one missionary, the purpose of the Girls' Boarding School (GBS) was to teach girls to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Similarly, John Taylor's (1958) account of the growth of the Church in Buganda suggested that among educated and urban women marriage ages had increased during the colonial era. Further narrative evidence from a Quaker mission's boarding school in Western Kenya suggests that female education, despite its strong emphasis on domesticity increased girls' control over their choice of marriage partner, postponing marriage for schoolgirls relative to girls living outside the mission (Thomas 2000). Parallel to this, Perlman (1966) suggests that Ugandan fathers were beginning to lose control over their daughters because mission schools and churches provided opportunities for boys and girls to mingle, militating against arranged marriages.…”
Section: Felix Meier Zu Selhausenmentioning
confidence: 93%
“…Similarly, John Taylor's (1958) account of the growth of the Church in Buganda suggested that among educated and urban women marriage ages had increased during the colonial era. Further narrative evidence from a Quaker mission's boarding school in Western Kenya suggests that female education, despite its strong emphasis on domesticity increased girls' control over their choice of marriage partner, postponing marriage for schoolgirls relative to girls living outside the mission (Thomas 2000). Parallel to this, Perlman (1966) suggests that Ugandan fathers were beginning to lose control over their daughters because mission schools and churches provided opportunities for boys and girls to mingle, militating against arranged marriages.…”
Section: Felix Meier Zu Selhausenmentioning
confidence: 93%
“…Ideologically, the missionaries sought schools that would diffuse their concept of a humanitarian, just, and civilized society among West Africans (Murray 1935;Thomas 2000). They were also motivated by their ''... desire to give rather than to take, and to offer what they believed to be the best form of their own culture'' (Taylor 1984: 196).…”
Section: The Missionary Ideologymentioning
confidence: 98%
“…The missionary practice of renaming Africans led to disrespect or disregard of local names. As part of their cultural and religious conversion of Africans, the Missionaries required all converts to adopt a Christian name (Thomas 2000). In many cases, Africans continued this practice when they enrolled in government schools.…”
Section: The Phelps-stokes Report: Expansion and Reformmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in African women losing power. In other cases, previously marginalized women acquired wealth, status, power, and independence or freedom due to factors such as conversion to Christianity, urbanization, female migration, freedom of sexual choice outside the lineage (see White 1990; Barnes and Win 1992;Schmidt 1992;Jeater 1993;Thomas 2000), and Western education in relation to the accompanying monetization of African economies. In some cases, the intersection of external factors with traditional social organization and gender roles and relations resulted in previously powerful women losing their power (see van Allen 1976).…”
Section: Femininities In African Contextsmentioning
confidence: 99%